Design and Characterization of Microscale Auxetic and Anisotropic Structures Fabricated by Multiphoton Lithography - Ioannis Spanos; Zacharias Vangelatos; Costas Grigoropoulos; Maria Farsari (Nanomaterials, 2021)
The need for control of the elastic properties of architected materials has been accentuated due to the advances in modelling and characterization. Among the plethora of unconventional mechanical responses, controlled anisotropy and auxeticity have been promulgated as a new avenue in bioengineering applications. This paper aims to delineate the mechanical performance of characteristic auxetic and anisotropic designs fabricated by multiphoton lithography. Through finite element analysis the distinct responses of representative topologies are conveyed. In addition, nanoindentation experiments observed in-situ through scanning electron microscopy enable the validation of the modeling and the observation of the anisotropic or auxetic phenomena. Our results herald how these categories of architected materials can be investigated at the microscale.